Tinjauan Potensi dan Kebijakan Energi Surya di Indonesia - Faisal Afif; Awaludin Martin (Proklamasi 45 University, 2022)
The need for electrical energy in Indonesia is always increasing from year to year. The State Electricity Company in Indonesia (PLN), said that the national electricity demand in 2018 was 232,296 TWh and will increase 5.1% every year. However, energy sources are still dominated by coal and fossil fuels at 59.6%. The potential for renewable energy from solar energy is currently not widely used, even though the potential for renewable energy is very large, especially in Indonesia. This paper purpose to provide information about the potential of solar energy that can be utilized especially as a power plant and the policies and constraints of solar power plants in Indonesia. Indonesia has a fairly stable distribution of solar radiation throughout the year. The government has targeted the installed capacity of solar energy for power plant to reach 0.87 GW by 2025. Realization of Solar Power Plants (PLTS) in 2020 reached 0.15 GWp from the potential of solar energy in Indonesia of 207.8 GWp. Researchers, academics, and the government also continue to develop and innovate of solar energy technology in Indonesia and are expected to maximize the use of Renewable Energy. Some of the obstacles experienced are the high investment costs that must be incurred, causing the price of electricity produced from renewable energy to become uneconomical.